The Influence of Business Capital, Intellectual Capital, Accounting Information Systems, Entrepreneurial Attitude, and Market Orientation on the Performance of MSMEs in Padang City (Case Study of Packaged Culinary in Bungus Teluk Kabung District, Padang City) - Nadia Salbila Putri; Ansofino; Jolianis (Journal of Practice Learning and Educational Development, 2026)
This research aims to analyze 1) the influence of business capital on MSME performance, 2) the influence of intellectual capital on MSME performance, 3) the influence of accounting information systems on MSME performance, 4) the influence of entrepreneurial attitude on MSME performance, 5) the influence of market orientation on MSME performance, and 6) the combined influence of business capital, intellectual capital, accounting information systems, entrepreneurial attitude, and market orientation on MSME performance in Padang City. This type of research is associative research. The research population consists of culinary MSME entrepreneurs in Lubuk Kilangan, Padang City, totaling 120 samples. The sampling technique used is purposive sampling. The instrument used for the research is a closed questionnaire. The data analysis technique uses multiple linear regression tests. The research results show that: (1) there is a significant influence of business capital on the performance of MSMEs with a coefficient value of 0.028, a t-value of 2.463 > t-table value of 1.980; (2) there is a significant influence of intellectual capital on the performance of MSMEs with a coefficient value of 0.315, a t-value of 4.239 > t-table value of 1.980; (3) there is a significant influence of accounting information systems on the performance of MSMEs with a coefficient value of 0.212, a t-value of 2.135 > t-table value of 1.980; (4) there is a significant influence of entrepreneurial attitude on the performance of student MSMEs with a coefficient value of 0.220 and a t-value of 2.625 > t-table value of 1.980; (5) there is a significant influence of market orientation on the performance of student MSMEs with a coefficient value of 0.211 and a t-value of 3.169 > t-table value of 1.980; (6) there is an influence of working capital, intellectual capital, accounting information systems, entrepreneurial attitude, and market orientation collectively on the performance of SMEs with F count 59.336 > F table 2.45.